2018
DOI: 10.3892/or.2018.6742
|View full text |Cite
|
Sign up to set email alerts
|

Copine�5 expression predicts prognosis following curative resection of esophageal squamous cell carcinoma

Abstract: Patients with esophageal squamous cell carcinoma (ESCC) have a poor prognosis. Identification of biomarkers to accurately predict the risk of recurrence and survival following curative esophageal resection is required to improve patient outcomes. The copine 5 (CPNE5) gene encodes a calcium-dependent lipid-binding intracellular protein. Copine proteins interact with diverse target proteins that are components of pathways that aberrantly regulate the phenotypes of malignant cells. However, limited information is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Moreover, low CPNE5 expression potentially promotes the local growth of esophageal cancer and increases resistance to chemotherapy drugs. These findings suggest that CPNE5 can be used as a biomarker for predicting ESCC recurrence, especially in patients with local recurrence, and can help ensure that patients receive optimal treatment and follow-up (Umeda et al, 2018). It is also reported that multiple myeloma (MM) patients with higher CPNE5 expressions had longer event-free survival and overall survival, suggesting that CPNE5 might be used as a positive indicator for MM (Yang et al, 2018).…”
Section: Cpne5mentioning
confidence: 83%
“…Moreover, low CPNE5 expression potentially promotes the local growth of esophageal cancer and increases resistance to chemotherapy drugs. These findings suggest that CPNE5 can be used as a biomarker for predicting ESCC recurrence, especially in patients with local recurrence, and can help ensure that patients receive optimal treatment and follow-up (Umeda et al, 2018). It is also reported that multiple myeloma (MM) patients with higher CPNE5 expressions had longer event-free survival and overall survival, suggesting that CPNE5 might be used as a positive indicator for MM (Yang et al, 2018).…”
Section: Cpne5mentioning
confidence: 83%
“…It is hypothesized to be a negative regulator of cell proliferation in aggressive acute myelogenous leukemia [51]. Other members of the copine protein family-copine I, III, and V-have been shown to promote several cancers' migration and growth potentials [52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…analysis. The levels of STRA6 mRNA in clinical samples were determined in triplicate using RT-PCR analysis as previously described (13,14). The STRA6 primers were as follows: forward 5'-CTATGGCAGCTGGTACATCG-3' and reverse 5'-TACAG GCCGGGTGGTATG-3'.…”
Section: Reverse-transcription Polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%